Developing engineering students’ empathy skills using serious games in project management : an exploratory study - Umawathy, Techanamurthy; Chuah, Kee Man; Ivan, Yee (Taylor and Francis Ltd., 2025)
This study explores the integration of serious games into engineering education to enhance empathy skills, a critical but often overlooked soft skill in technically focused curricula. Using a pretest-posttest quasi-experimental design, the research examines the effectiveness of the HR Toxic Workplace game, which simulates a toxic work environment to foster empathy and project management skills. Forty-nine engineering project management students from a Malaysian public university participated in four weeks of weekly gameplay sessions. Empathy was assessed using Davis’s Interpersonal Reactivity Index (IRI), which measures both cognitive and affective components across four subscales: Perspective Taking, Empathic Concern, Personal Distress, and Fantasy. Data were collected before and after the intervention through quantitative and qualitative instruments. Results indicate significant improvements in empa-thy, especially in the areas of perspective taking and personal distress. These outcomes demonstrate that serious games can provide immersive and interactive experiences that support empathy development, which traditional classroom methods may lack. This study adds to existing research on serious games in education and shows their value in addressing the empathy gap in engineering. It also suggests broader potential for gamified learning strategies in higher education.